Avaliação morfofuncional das espermatogônias de camundongos mutantes Utp14bjsd sob condições normais de temperatura testicular e após criptorquidismo experimental - Renata Cadete Zallio (2009)
This study evaluated parameters of the spermatogonial biology in Utp14bjsd-/- mutant mice. Up puberty the spermatogenic process is normal but in adulthood spermatogonial differentiation fail becoming the mice azoospermic. Moreover, it is known that when the testicles of azoospermic animals are experimentally placed in the abdominal cavity, the temperature increases and restore spermatogonial differentiation. Using this mutant mouse as an experimental model, we evaluated in the present study changes in spermatogonial kinetic such as (a) number of spermatogonia and their (b) mitosis and (c) apoptosis, as wellas (d) morphology of cells, comparing heterozygous and jsd mutant mice and the effects of temperature, after 7 days of experimental cryptorchidism. These morphological and morphometric evaluations were taken using high resolution light microscopy method, wherethe testes were fixed with glutaraldehyde / osmium, embedded in alraldite resin cut with 1m of thickness and stained with toluidine blue-sodium borate. It was observed that experimental cryptorchidism causes nuclear morphological changes in spermatogonia of jsd+/-, mice,which are phenotypically normal, and emphasizes the morphological alteration in jsd mutant mice. It was also observed that the experimental cryptorchidism for 7 days mainly affected undifferentiated spermatogonia as compared to the kinetics of other spermatogonial types (from A1 to B) in which their number was proportionally reduced. It was seen that thecryptorchidism acted differently on the spermatogonial proliferation, that is, whereas in jsd+/- inhibited in jsd-/- mutant mice stimulated spermatogonial mitosis, being able to restore the spermatogenic process. In jsd mutant mice, the higher teticular temperature increases the number of undifferentiated spermatogonia with a progressive increases of the spermatogonial number from type A3 spermatogonia. It was observed in heterozygous mice the presence of two type Aind spermatogonia populations concern their sensitive to thetesticular temperature, caused by cryptorchidism: those without nuclear vacuoles that reduce their number after cryptorchidism and those with nuclear vacuoles that maintains the same number even when the testicle is placed inside the abdominal cavity. This found suggests that in heterozygous mice type Aind spermatogonia with nuclear vacuole either are in a phase of cell cycle refractory for the temperature effects or they are a spermatogonial population different from those without nuclear vacuoles.